Nickel-Catalyzed Asymmetric Synthesis of P-Stereogenic Vinyl Phosphines - Liu, Xu-Teng; Wu, Yue; Zhang, Qing-Wei (Synlett, 2021)
Addition reaction to alkynes is an efficient strategy for constructing valuable alkenyl compounds. However, the elusive regioselectivity has been a persistent challenge. In the context of hydrophosphination reaction which could afford valuable P-stereogenic phosphines, the control of enantioselectivity as well as regioselectivity were especially tricky. Here, we highlighted our recent work on the nickel-catalyzed regio- and enantioselective hydrophosphination of unactivated alkynes with in situ generated secondary phosphines.1 Introduction2 Hydrophosphination of Alkynes3 Derivatization Reactions4 Mechanism Research5 Summary and Outlook
Keywords: P-stereogenic; phosphine compounds; nickel catalysis; hydrophosphination; transition metals